Pharmacies' income and its effective factors in Iran: A cross‐sectional study - Mohsen Bayati; Ahmad Gholami; Mehrnoosh Emadi; Zahra Goudarzi; Khosro Keshavarz (Health Science Reports, 2023)
Abstract Purpose Financial assessment of pharmacies and the factors affecting it is an important issue in health system and pharmaceutical industry. The present study aimed to analyze the revenue of pharmacies in Iran and the factors affecting it. Methods In the present study revenue data of all active pharmacies in Shiraz in 2018 (n = 298) were gathered using a checklist. Descriptive statistics, mean difference test, correlation, and regression analysis were performed for statistical evaluation. Heteroskedasticity and multicollinearity also were checked. Stata 15 was used for statistical analysis. Results Average monthly income of the pharmacies was $82,879 USD (SD = 30,635). The monthly revenue of 24 h pharmacies was about $6560 higher than that of the daily pharmacies. The pharmacies founded by non‐pharmacists made about $44,038 more than others, and the pharmacies located on main streets earned over $84,247 more than the ones located on side streets. Besides, the pharmacies inside or near hospitals, clinics, or physician buildings made more money than others. Correlation analysis also showed that the pharmacies' working years, the number of adjacent pharmacies, the number of OTC prescriptions, and the number of staff working at the cosmetics counters had a positive relationship with the pharmacies' income. Conclusions Final findings indicated that 24 h pharmacies, pharmacies located on main streets, the ones located in hospitals or private clinics and physician buildings, pharmacies with more OTC prescriptions, and the ones with a larger number of employees in the cosmetics departments had higher monthly revenues.